Symposium on Muslims in Europe - Abdulaziz Sachedina (International Institute of Islamic Thought, 1992)
The question of a Muslim minority in the Western context has become an important one in view of some h-and-hysteria literatu~th at continues to depict this minority as a threat to Western liberal values and sociopolitical systems. The conference papers were structured around a basic theme of “Muslims, Islam, and Diaspora,” which reveals the difficulty of European scholars as well as government officials in accurately conceptualizing the Muslim experience of immigration in the West. To be sure, there is no concept of an eschatological ”promised land” or “holy land” in the Qur’an to suggest “diaspora” - the dispersion of its adherents from it - even in the remotest sense of the term. The entire earth, according to the Qur’an, belongs to God and has been created for humanity to seek its own advancement towards the moral and spiritual goals wherever it so chooses, as long as no injustices are committed against fellow humans beings. The concept of dZir al hijrah, on the other hand, captures the spirit of Muslim emigration to the West. It is a journey undertaken to overcome spiritual and moral “homelessness,” a physical transferral to the sphere which holds out the promise of deviatiog the unfavorable conditions prevalent in one’s awn place of domicile. To this early meaning of emigration (hijrah) of a person from a particular place or set of surroundings to seek protection is added emigration for the sake of economic advantage, either temporanly or permanently, somewhere else. In other words, for Muslims this sphere of emigration is not what Europe wants to perceive, namely, a “diaspora” that would make them endeavor to return from the “diaspora” to their “holy land” located somewhere in Arabia. Apart from this lack of conceptual clarity in categorizing the Muslims’ perception of their spatial relationship in the West, European scholars and administrators are faced with another difficulty. This was discussed by Reinhard Schulze following his paper on ”International Organization and Muslims in Europe.” Schulze pointed out the inadequacy with which Europe defines the word “religion” and then imposes it on Islam, expecting to discover a central Islamic “church” headed by a Muslim “bishop” with whom the government can establish administrative relations. Even more difficult for homogenous European nations like France, where the majority is Catholic, is to recognize the existence of other “religions“ besides Christianity for administrative purposes. This difficulty is self-created, because such recognition entails empowering the followers of other ...